French subject island? Empirical studies of dont and de qui - Abeillé, Anne; Winckel, Elodie (Journal of French language studies, 2020)
Dont has been claimed to be an exception to the ‘subject island’ constraint (Tellier, 1991; Sportiche and Bellier, 1989; Heck, 2009) and to contrast with true relative pronouns such as de qui. We provide corpus data from a literary corpus (Frantext), which show that relativizing out of the subject is possible with dont and de qui in French relative clauses, and is even the most frequent use of both relative clauses. We show that it is not a recent innovation by comparing subcorpora from the beginning of the twentieth century and from the beginning of the twenty-first century. We also show, with an acceptability judgement task, that extraction out of the subject with de qui is well accepted. Why has this possibility been overlooked? We suggest that it may be because de qui relatives in general are less frequent than dont relatives (about 60 times less in our corpus). Turning to de qui interrogatives, we show that extraction out of the subject is not attested, and propose an explanation of the contrast with relative clauses. We conclude that in this respect, French does not seem to differ from other Romance languages.